Clustering‐Induced White Light Emission from Carbonized Polymer Dots. Issue 5 (12th March 2021) - Liu, Bin; Chen, Zheng; Chu, Bo; Wang, Ya-Ling; Li, Ning; Zhang, Huinian; Yang, Yongzhen; Hu, Shengliang; Zhang, Xing-Hong
Abstract : Despite the advancements in synthetic methods, it is still challenging to prepare white light‐emitting carbon dots for solid‐state white light‐emitting diodes (LEDs). Herein, the synthesis and characterization of a carbonized polymer dot (CPD) that emits white light in the solid state are presented. The reaction of an oxygen‐rich precursor, trimethylolpropane tri(cyclic carbonate) ether, with nitrogen‐rich melamine in an alcohol via a single‐step solvothermal method affords CPDs with hydroxyurethane and CN groups. The morphology of the CPDs can be regulated by changing the reaction time. Transmission electron microscopy reveals structural evolution from flocculent polymers to dandelion‐like and spherical particles with an increase in the carbonization time from 6 to 12 and 18 h, respectively. The dandelion‐like CPDs exhibit a relatively high quantum yield of 7.5% in the solid state, which is ascribed to the abundant surface poly(hydroxyurethane) chains that restrict the aggregation‐caused quenching of luminescence. It is proposed that multiple coexistent clusters generate different emission sites, thereby leading to white light emission. Loose clusters formed from hydroxyurethane and CN bonds, which have a low degree of conjugation, emit blue light, whereas compact clusters generated through interactions between the hydroxyurethane and CN bonds of poly(hydroxyurethane) and carbon cores emit yellow light. Abstract : A carbonized polymer dot that emits white light in the solid state is prepared from trimethylolpropane tri(cyclic carbonate) ether and melamine as precursors by a one‐step solvothermal method. A multi‐cluster‐induced luminescence mechanism is proposed to account for the observed luminescence.